2014
DOI: 10.1088/1468-6996/15/3/035013
|View full text |Cite
|
Sign up to set email alerts
|

Silica based polishing of {100} and {111} single crystal diamond

Abstract: Diamond is one of the hardest and most difficult to polish materials. In this paper, the polishing of {111} and {100} single crystal diamond surfaces by standard chemical mechanical polishing, as used in the silicon industry, is demonstrated. A Logitech Tribo Chemical Mechanical Polishing system with Logitech SF1 Syton and a polyurethane/polyester polishing pad was used. A reduction in roughness from 0.92 to 0.23 nm root mean square and 0.31 to 0.09 nm rms for {100} and {111} samples respectively was observed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The polishing technique and proposed mechanisms are well described elsewhere [22,23,27]. Prior to polishing, the felt pad was roughened with a chuck embedded with diamond grit for 30 min to promote the surface texture optimally required for polishing [28].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The polishing technique and proposed mechanisms are well described elsewhere [22,23,27]. Prior to polishing, the felt pad was roughened with a chuck embedded with diamond grit for 30 min to promote the surface texture optimally required for polishing [28].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For the purposes of polishing a series of ≈350nm thick diamond films were grown atop silicon dioxide buffered silicon substrates using the process detailed within a previous study [22]. Atomic force microscopy (AFM) scans were then Before polishing, the pads were conditioned for 30mins with a conditioning chuck which consists of nickel plate embedded with diamond grit and polishing slurry to facilitate the polishing and slurry distribution [21,24]. For polishing the films, both the pad and wafer carrier were rotated at 60rpm opposite to each other with carrier sweeping across the pad.…”
Section: Methodsmentioning
confidence: 99%
“…While this had no effect on roughness (table 1), termination-induced lattice charging during annealing could affect the NV creation process 28 . Two samples (Cmp1 and Cmp2) were processed in a recently developed chemical mechanical polishing (CMP) process employing a fluid of silica nanoparticles 30,34 . On these samples we observe point-like defects rather than grooves, and one of them shows a significantly reduced roughness of rms = 0.51 nm (Cmp2, Figure 2d).…”
Section: Methodsmentioning
confidence: 99%
“…So far, no systematic study of influence of the surface geometry has been reported. It is known that different polishing techniques can yield surface roughnesses varying by two orders of magnitude 29 , with the best results approaching smoothness on the atomic level [30][31][32] . We therefore investigated the influence of different polishes on the coherence time T2 of shallow implanted NVs.…”
Section: Introductionmentioning
confidence: 99%